Analisis Sistem Informasi Akuntansi Utang Pada PT Mifa Bersaudara - Ardevi, Devi; Rahmadani, Ika (Universitas Teuku Umar, 2024)
The aim of this research is to analyze the debt accounting information system implemented at PT Mifa Bersaudara and what are the obstacles to delays in debt payments. This research uses a qualitative descriptive method that systematically describes the debt accounting information system at PT Mifa Brothers. Data collection techniques include direct observation, interviews and documentation. The results of this research indicate that the accounting information system implemented by PT Mifa Brothers is in accordance with existing theory. However, there are still delays in the debt payment process. Factors causing delays in debt payments are sales and collection of funds by the treasury.